The Relationship Between Physical Activity, Stress Level, and Eating Habits on the Incidence of Gastritis in Adolescents at the Outpatient Polyclinic: A Cross-sectional Study - Afriansyah, M; Parmin, Selamat; Safitri, Serli Wulan; Saputra, Andre Utama (Lentera Perawat, 2025)
Gastritis in adolescents is increasingly common due to lifestyle changes, stress, and poor eating habits. This disorder can interfere with quality of life and academic achievement. This study aims to analyze the relationship between physical activity, stress levels, and eating habits with the incidence of gastritis in adolescents. This study used a descriptive correlational design with a cross-sectional approach. The sample consisted of 86 adolescents who sought treatment at the South Sumatra Police Headquarters Outpatient Polyclinic in June 2024. Data were collected through structured questionnaires and medical records. The majority of respondents experienced gastritis (57.0%), with a higher proportion in adolescents who had moderate physical activity (p = 0.029), moderate stress levels (p = 0.001), and poor eating habits (p = 0.004). There is a significant association between physical activity, stress, and eating habits with the incidence of gastritis in adolescents. Holistic intervention is needed through nutrition education, stress management, and promotion of healthy lifestyle in school and family environment.